RITUALISERET TALE I HOVEDLØSE SAMFUND - Veber, Hanne (Tidsskriftet Antropologi, 1997)
Hanne Veber: Ritualized Speech in Headless Societies. The Constitution of Power and Publicness in the Amazon Anthropology conceptualizes native Amazonians as prototypical egalitarian societies. In these societies, formal leadership is weak and seldom operative beyond the extended family or local group level. It is based on personal prestige and the ability to inspire confidence. The leader is expected to guide his following through the topography of the economic and the socio-political landscapes but is in no position to give orders or command. This weak power syndrome has inspired the term “headless society” in the literature. Pierre Clastres has developed the idea that a systematic antistate campaign is embedded in Amazonian social structure and therefore, centralization and consolidation of power has been precluded. Short of subscribing to Clastres’ argument, it is clear that power in Amazonian societies, as elsewhere, is based on consent and this fumishes the only measure of its legitimacy. The questions remain, then, how is order constituted in the absence of explicit mechanisms for enforcement of rules and norms, and how are potential conflicts solved? One answer is furnished by the institution of ritualized speech or ceremonial dialogue found in most Amazonian societies. These constitute devices of meta-communication through which human interaction is regularized. Years ago, the Danish anthropologist Niels Fock explored the Waiwai oho-chant as a form of legal authority in Weber’s sense, supplementing the traditional authority on which Waiwai leadership rested. The relation between the two forms of authority remained unclear, however. Greg Urban views ceremonial dialogue through the optics of semiotics and demonstrates its regulative social functions, thus providing a sophisticated confirmation of Fock’s earlier hypothesis. Comparative data on ritualized speech from the author’s fieldwork among the Pajonal Asheninka of eastem Peru demonstrates how potential conflicts are negotiated through ritualized speech and how the resolutions are confirmed through their being made public by the ritualization. In this sense ritualized speech facilitates a smooth flow of social life - even in the societies with no head.